Evaluasi Kualitas Estetika Taman Balekambang Solo berdasarkan Pengalaman Berkunjung - Rahmawati, Erlitha; Pudjihartati, Endang (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022, 2022)
Evaluation of the aesthetic quality of Balekambang Solo Park based on visiting experience. Big Cities such as Solo City have green open spaces such as the Balekambang Park, safe anda beautiful park is the main point to be likes by people. Aesthetic quality is one of the factor that everything becomes beautiful. The aim of this research is to evaluate the aesthethic quality of Balekambang Park Solo based on the experience of traveling. Method this research was conducted by taking landscape photos and performing aesthetic quality assessments by distributing online questionnaires. Then, a division of respondents who had been visited was carried out with responden who had never been. The results of the aesthetics quality evaluation, based on the experience of visiting, makes a difference. The differences can be seen in several areas of Balekambang Park such as the Playground Area . Partinah Bosch Area, Rocky Road Area, Open Space Area anda Artificial Lake Area. The Playground Area there area 2 landscape that have different results, Partinah Bosch  Area has 4 landscape, Rocky Road Area has 2 landscape, Open Space area has 3 landscape, and Artificial Lake area has 2 landascape. The difference in these results can be caused that respondents who have not vivisted only judge form the picture, while respondents who visit the area understand the layout or location the area so that they can remember the uniqueness and the condition of the area.